Problematika Pembelajaran Membaca dan Menulis di Sekolah Dasar - Ketut Bali Sastrawan (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2018)
Reading and writing is one of the most important activities in learning and can be said all the learning process on the ability to read and write. This phenomenon can happen during this time, be parents more able to be able to read even before entering primary school. The ability to read and write, still active at the preoperational stage (2 - 6 years). Stages of thedevelopment of reading and writing ability that can be controlled by children aged 2-6 years. Children need to be trained with. To overcome the difficulty of reading can be done various kinds of things in accordance with factors that affect these students who have difficulty reading. In particular to overcome this, in schools teachers who also act as a facilitator can do coaching to students who have difficulty reading.Keywords : Reading, Writing, Problematic, Learning, Primary School